Case Report: Massive intrapericardial hematoma following acupuncture therapy - Chen, Weiguang; Gao, Xiaoling; Li, Hong (Frontiers in Cardiovascular Medicine, 2024)
Cardiac tamponade is a critical cardiovascular condition where timely diagnosis and treatment are crucial. The formation of an intrapericardial hematoma following acupuncture therapy is clinically rare. This paper reports a case of an elderly female patient who experienced severe chest pain and syncope during acupuncture therapy, subsequently diagnosed with traumatic hemopericardium and acute cardiac tamponade, complicated by cardiogenic shock. Under ultrasound guidance, pericardial puncture and drainage were successfully performed. The patient's symptoms were alleviated, her vital signs stabilized, and follow-up outcomes were favorable. This case provides valuable reference for understanding the pathogenesis, diagnosis, and treatment of pericardial hemorrhage following acupuncture therapy, integrating both clinical practice and literature review.